OPTIMIZING GENERATION Z MOBILITY THROUGH CULTURAL TOURISM IN BAUBAU CITY: BUILDING INTERCULTURAL COMMUNICATION IN THE DIGITAL ERA - Nurfida, Wa; Mayunita, Sry; Ulfa, Maria; Hastuti, Hastuti; Ferdana, Zahwa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Generation Z as active users of digital technology, tends to be disconnected from local cultural values, so an approach that combines culture and technology is needed to create a higher cultural awareness. The purpose of this study is to analyze the impact of cultural tourism activities on intercultural understanding and communication among Generation Z in Baubau. The method used in this study is a qualitative approach with observation techniques, in-depth interviews, and surveys of cultural tourism program participants. The data obtained were analyzed to assess changes in cultural understanding, active participa tion, and intercultural interaction through digital media. The results show that this cultural tourism program successfully increased Generation Z's interest in local cultural heritage and strengthened intercultural communication through digital platforms. Participants demonstrated an increased understanding of cultural diversity and were able to use social media to share cultural experiences, which in turn created more inclusive interactions and opened up space for more constructive intercultural dialogue. This research contributes to the development of a cultural tourism model that is relevant for Generation Z in the digital era.